Managing winning proposals : the fundamentals - Frieman, Wendy (Routledge, 2026)
"Preparing a proposal for a contract or a grant can be an overwhelming and extraordinarily complex process, but regardless of the proposal type or sector, certain truths always pertain. This book walks the proposal manager through the steps that are essential and common to every single proposal and ensure a foundation for winning. Many proposal management books are of little use, particularly to a first-time proposal manager, due to their broad scope and unrealistic assumptions about resources including time, expertise, and information. This book provides actionable, concrete steps for the activities that underpin all successful proposals, providing a step-by-step description of how to make a proposal compliant and compelling. The premise of the book, based on the author's more than three decades of hands-on experience in multiple proposal roles, is that proposals do not go off the rails due to an inability to implement advanced techniques and complicated processes. They fail because of inattention to fundamental activities. Other business books cover some of these fundamental activities. However, proposals differ because of their tight constraints: deadlines, the need for perfect compliance with detailed instructions, fierce competition for limited funds, the consequences of not winning, and the stress that inevitably accompanies the process. Focusing solely on the preparation of the written proposal document and not on sales, negotiation, marketing, or customer interaction, this book dives into the details of the tasks facing the person actually accountable and responsible for preparation and delivery of the proposal. Proposal managers of all levels, from first-timers to seasoned pros looking to polish their skills, as well as those who participate in the proposal process but are not intimately familiar with it-artists, technical writers, project managers, accountants, and others-will benefit from the processes and tools described in this book"-- Provided by publisher.